An Msx2-Sp6-Follistatin Pathway Operates During Late Stages of Tooth Development to Control Amelogenesis - Ruspita, Intan; Das, Pragnya; Xia, Yan; Kelangi, Sarah; Miyoshi, Keiko; Noma, Takafumi; Snead, Malcolm L.; D’Souza, Rena N.; Bei, Marianna (Frontiers in Physiology, 2020)
Background: Ameloblasts are epithelially derived cells responsible for enamel formation through a process known as amelogenesis. Amongst the several transcription factors that are expressed during amelogenesis, both Msx2 and Sp6 transcription factors play important role. Msx2 and Sp6 mouse mutants, exhibit similar amelogenesis defects, namely enamel hypoplasia, while humans with amelogenesis imperfecta AI carry mutations in the human homologues of MSX2 or SP6 genes. These across species similarities in function indicate that these two transcription factors may reside in the same developmental pathway. In this paper, we test whether they work in a coordinated manner to exert their effect during amelogenesis. Methods: Two different dental epithelial cell lines, the mouse LS8 and the rat G5 were used for either overexpression or silencing of Msx2 or Sp6 or both. Msx2 mutant mouse embryos or pups were used for in vivo studies. In situ hybridization, semi-quantitative and quantitative real time PCR were employed to study gene expression pattern. MatInspector was used to identify several potential putative Msx2 binding sites upstream of the murine Sp6 promoter region. Chromatin Immunoprecipitation was used to confirm the binding of Msx2 to Sp6 promoter at the putative sites. Results: Using the above methods we identified that (i) Msx2 and Sp6 exhibit overlapping expression in secretory ameloblasts (ii) Sp6 expression is reduced in the Msx2 mouse mutant secretoty ameloblasts and (iii) that Msx2, like Sp6 inhibits follistatin expression. Specifically, our loss-of function studies by silencing Msx2 and/or Sp6 in mouse dental epithelial (LS8) cells showed significant downregulation of Sp6 but upregulation of Fst expression. Transient transfection of Msx2 overexpression plasmid, up-regulated Sp6 and downregulated Fst expression. Additionally, using MatInspector, we identified several potential putative Msx2 binding sites, 3.5 Kb upstream of the murine Sp6 promoter region. By Chromatin Immunoprecipitation, we confirmed the binding of Msx2 to Sp6 promoter at these sites, thus suggesting that Sp6 is a direct target of Msx2. Conclusions: Collectively, these results show that Sp6 and Msx2 work in a concerted manner to form part of a network of transcription factors that operate during later stages of tooth development controlling ameloblast life cycle and amelogenesis.